Metacognitive strategy to increase vocabulary in EFL in 10th grade “C” students of basic education at “Mariscal Antonio José de Sucre” School. - Banda Bustillos, Marcia Rosalva (2021)
This research focuses on Metacognition, like the thinking skill, which leads up young students during the teaching-learning process by using the correct learning strategy to learn new vocabulary. Consequently, the purpose of this research is to analyze the Metacognitive strategy using in the English language to increase young students’ vocabulary of 10th grade “C” in the “Mariscal Antonio José de Sucre” Educative Unit. The applied methodology has a qualitative and a quantitative approach that includes a descriptive procedure of the Metacognitive strategy. These methods allow a collection of statistical data and information to establish conclusions and recommendations about the research. Considering that to learn and use the English Language in the teaching-learning process and real life, it is essential to dominating vocabulary; a group of students first went in a pre-test, after that they went through metacognitive strategy instruction to provide awareness of learning strategies finally; they went in a post-test. The results showed that the adequate application of the Metacognitive strategy in English classes increases vocabulary in young students, and they achieve higher levels of learning control to develop their knowledge and skills.